2020
DOI: 10.1017/s1092852919001585
|View full text |Cite
|
Sign up to set email alerts
|

A survey of national trends in psychiatric patients found incompetent to stand trial: reasons for the reinstitutionalization of people with serious mental illness in the United States

Abstract: Objective.Recent information indicates that the number of forensic patients in state hospitals has been increasing, largely driven by an increase in patients referred to state hospitals as incompetent to stand trial (IST). This survey was intended to broaden the understanding of IST population trends on a national level.Methods.The authors developed a 30-question survey to gather specific information on IST commitments in each state and the District of Columbia. The survey was administered to all 50 states and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In Virginia, site of the present study, court orders for stand-alone competence evaluations of adults increased 218% from 690 in 2007 to 1,507 in 2018 (unpublished data from the Virginia Department of Behavioral Health and Developmental Services provided July 22, 2020) 1 . Indeed, in a recent survey of forensic administrators and experts from nearly every state, 70% reported that they perceived referrals for competency evaluations of felony defendants were increasing, and 71% reported that they perceived referrals for competence evaluations of misdemeanor defendants were increasing (Warburton et al, 2020).…”
Section: Increasing Court Orders For Competence-related Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Virginia, site of the present study, court orders for stand-alone competence evaluations of adults increased 218% from 690 in 2007 to 1,507 in 2018 (unpublished data from the Virginia Department of Behavioral Health and Developmental Services provided July 22, 2020) 1 . Indeed, in a recent survey of forensic administrators and experts from nearly every state, 70% reported that they perceived referrals for competency evaluations of felony defendants were increasing, and 71% reported that they perceived referrals for competence evaluations of misdemeanor defendants were increasing (Warburton et al, 2020).…”
Section: Increasing Court Orders For Competence-related Servicesmentioning
confidence: 99%
“…The increase in IST cases is notably sharp in the most recent statistics available. From 2014 to 2015, IST cases increased by 48%. Similarly, in the recent survey of forensic administrators and experts from nearly every state, 65% reported that they perceived increased competence restoration orders for those defendants charged with felonies, and nearly 69% reported that they perceived increased restoration orders for defendants charged only with misdemeanors (Warburton et al, 2020).…”
Section: Increasing Court Orders For Competence-related Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of individuals with SMI found IST, in particular, has increased exponentially in recent years, leading to explosive growth in admissions to state psychiatric hospitals and an inability, in many states, to provide adequate and timely assessment and treatment (Callahan & Pinals, 2020). In a recent survey, 82% of states reported a significant increase in the numbers of individuals referred for evaluation of competency to stand trial (CST; Warburton et al, 2020), and data from the State Profiling System maintained by the National Association of State Mental Health Program Directors Research Institute suggest that the number of forensic patients in state psychiatric hospitals increased, on average, by 76% between 1999 and 2014, primarily due to an increase in the numbers of individuals found IST (Wik et al, 2020). Limited space, due to reductions in available inpatient psychiatric beds (Gao, 2021), as well as a shortage of skilled assessors and overwhelming demand, has led to significant delays in both assessment and treatment (Callahan & Pinals, 2020).…”
Section: Competence To Stand Trialmentioning
confidence: 99%
“…For example, the United States District Court of Washington case of Trueblood, et al v. Washington State Department of Health and Human Services et al 7 (2015) found that it is a violation of due process for defendants adjudicated incompetent to be held in jail for longer than 7 days awaiting competency restoration services. In California, a recent Superior Court order in the case of Stiavetti, et al v. Ahlin, et al 8 (2016) imposed a 28-day limit to the time a defendant can await competency restoration services, and this trend in litigation can be seen throughout the United States as jails are filling with patients awaiting state hospital admissions (Warburton et al, 9 in press). As such, alternatives to state hospitalization for IST patients have been developed, including communitybased restoration programs, and jail-based competency (JBCT) restoration programs.…”
Section: Introductionmentioning
confidence: 99%